Efficacy of 18-fluoro deoxy glucose-positron emission tomography computed tomography for the detection of colonic neoplasia proximal to obstructing colorectal cancer. Issue 31 (August 2018) - Hojo, Daisuke; Tanaka, Toshiaki; Takahashi, Miwako; Murono, Koji; Emoto, Shigenobu; Kaneko, Manabu; Sasaki, Kazuhito; Otani, Kensuke; Nishikawa, Takeshi; Hata, Keisuke; Kawai, Kazushige; Momose, Toshimitsu; et al.
Abstract : Abstract: Identification of secondary colonic neoplasia proximal to obstructing colorectal cancer is essential for determining the range of colorectal resection. We examined the accuracy of 18-fluoro deoxy glucose-positron emission tomography (FDG-PET) for detection of colonic neoplasia. We recruited patients with obstructing colorectal cancer from our registry. Preoperative FDG-PET was performed, and the detection rate for colonic neoplasia was estimated. Preoperative colonoscopy or postoperative colonoscopy within a year after operation was employed as the indexed standard. Ninety-three patients were included in this study. Colonic neoplasia proximal to obstruction was confirmed in 83 cases. The sensitivity and positive predictive value of FDG-PET were 25.3% and 77.8%, respectively. The sensitivity was higher in larger lesions (3.2% for <5 mm, 29.4% for 6–10 mm, 45.5% for 11–20 mm, and 71.4% for >21 mm) and in higher pathological grade lesions (14.6% for low-grade adenoma, 38.5% for high-grade adenoma, 66.7% for carcinoma in situ, and 100% for invasive carcinoma). The round shape in PET images was a predictor for neoplasia, with an area under the curve of 0.75293 at an aspect ratio of 1.70. FDG-PET should be used as a screening modality for invasive colorectal cancer (CRC) proximal to obstructing colorectal cancer.